Gamete Alteration of the Long-Spined Sea Urchin Diadema setosum (Leske, 1778) from Sichang Island, Chonburi Province, Thailand: A Preliminary Study - เสนารัตน์, ศิลปชัย; สุขใส, สุชารัตน์; กำเนิดนิล, ทัตพล; เกษตระทัต, เจษฏ์; ทองบุญ, ละม้าย; จิรอังกูรสกุล, วรรณีย์; ภารา, ชำนาญ; พูลประเสริฐ, พิสิษฐ์; เพ็งสกุล, ธีรกมล (YRU Journal of Science and Technology, 2018)
In this study, we selected the long-spined sea urchin, Diadema setosum, as sentinel species to investigate its gamete alteration to predict its reproductive health, from Sichang island, Chonburi province, Thailand. Ten adult samples including five male and five females were collected from February to May 2017. Redial measurement, gonadosomatic index (GSI) and collection of the testes and ovaries to observe the type and changes of the gametogenesis based on standard histological technique. The results revealed that redial measurement of the male D. setosum was 7.36±0.34 cm. and 7.36±0.78 cm. in the female D. setosum. The GSI of the male and female D. setosum were 9.85±4.6 and 10.70±4.16, respectively. Also, the gonadal development of both sexes was considered to be a growing stage. Several germ cells including spermatocyte, spermatid and spermatozoon in male D. setosum were observed, whereas previtellogenic stage was only occurred in female D. setosum. Interestingly, histopathological alteration was only found in the ovarian tissue of female D. setosum, especially in the appearance of the atretic pre-vitellogenic stage. From this preliminary study, it appeared that female D. setosum was in a potential risk to a reduction in oocytes, probably leading to a decline in the ovarian health. The influential factors in the fertility of female sea urchin Diadema setosum will be examined in further studies.